Dari Aniem Ke Ebalom: Jejak Listrik Dalam Perkembangan Kota Singaraja Pada Masa Kolonial Serta Potensinya Sebagai Sumber Belajar Sejarah Di SMA: Dari Aniem Ke Ebalom: Jejak Listrik Dalam Perkembangan Kota Singaraja Pada Masa Kolonial Serta Potensinya Sebagai Sumber Belajar Sejarah Di SMA - Luttfy Chateriyan, Ivan; Purnawati, Desak Made Oka; Arta, Ketut Sedana; Purnawibawa, R. Ahmad Ginanjar (Widya Winayata : Jurnal Pendidikan Sejarah, 2023)
Singaraja City is a city that has a long historical story. In 1849 it was conquered by the Dutch and then brought changes to the city structure in Singaraja. This is because the Singaraja City area has many natural resource commodities, the Dutch then wanted to make Singaraja City an economic, governmental, social center and so on. The city of Singaraja was made the center of the capital of the Lesser Sundas so that a lot of changes were made by the Dutch regarding urban structures and functions such as making many public facilities related to the economy, government, social and others. One example is electricity, the existence of electricity in Singaraja City cannot be released by the Dutch colonialists because they brought electricity to Singaraja City. This is evidenced by the existence of 3 electrical substations which have Dutch colonial characteristics. This electricity has a big impact on the development of the city of Singaraja, at this stage the community changes from rural to urban. Changes in the structure of the city have also turned into complexity, there are many special areas so this can be evidence of changes in the city due to electricity in the city of Singaraja. This study related to the history of the city of Singaraja is important to do because it can be used as a learning resource for high school students. Knowledge of history on things that are often encountered by students so that they can make knowledge of the importance of history for people's lives. Then in the tourism aspect it is also important because it can make the city of Singaraja also a city historical tour that gives the impression or feel of living in the past